Teaching supervisory control based on a web portal and a system of laboratory tasks - Landryová, Lenka (2006)
This paper was written based on experience with teaching subjects on control systems and industrial automation at technical universities. The paper presents proven methods on how to organize and moderate an educational process with an active participation of students during theoretical and practical work over the web. Such an approach does not limit the number nor the location of participants-students, teachers or consultant workers. The international and multicultural dimension is also the most challenging one, since the cooperation can be worldwide. The work with students requires a continuous development of syllabi, since the evolution and adaptation to the changing world is continuous too. The system is open to all the participants and the nature of all of the parties involved in the system can be corporate, scientific, social or educational. The software tools used for the area of supervisory control are presented in the paper, as well as ways on how to promote this work so that new members can use it.